PERLINDUNGAN HUKUM ATAS MEREK TERKENAL (WELL-KNOWN MARK) BERKAITAN DENGAN PELANGGARAN MEREK - Agus Bram Rendrajaya, Kadek; Rai Djaya, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper entitled “ Legal Protection of Well Known Brand” which related with brand infringement. This paper used normative method. The use of well known Brand in Indonesia without Owner’ permission is very detrimental to well known Brand owners. The efforts than can be done when the brand Infringement arise regulated in the law number 15, 2001 about Brand
Keywords: Well Known Brand, Infringement